P224 Agile, design led approach to online service development. (8th June 2017) - Howroyd, Chris; Baraitser, Paula; Courtenay, Molly; Parry, Glyn; Holdsworth, Gillian
Abstract : Introduction: Sexual health services lead innovative thinking in the NHS with integrated service provision, online access and testing in non-traditional venues. Agile design-led thinking creates services that are intuitive, easy to use and valued by users (both staff and patients). It offers an alternative to pre-specifying a whole system (waterfall approach) frequently associated with unpredicted problems, identified late and requiring costly fixes. Methods: SH:24 uses an agile, design-led approach to service development delivering value by: Focusing on user need (understanding and empathising rather than assuming); Reducing cost (failing quickly, cheaply); Reducing risk (avoiding unnecessary, costly development); Creating tangible, visual, measurable outputs early (promoting understanding, collaboration and buy-in). Our agile, design-led approach included extensive user involvement; building the minimum from cycles of build, test, learn; responding to feedback, continuously improving and optimising. Results: This presentation will provide three examples describing the contribution of agile to development of: 1. Self-sampling kit instructions which delivered 76–84% return rate 2. User friendly information pages on contraception – 2000 hits daily 3. Online chlamydia treatment – 95% uptake We will demonstrate the added value of design and agile for these examples. Discussion: An agile design led approach is championed by Government Digital Services - it involves re-framing issues as opportunities and rapidly iterating thinking by building and testing user centred prototypes - this approach minimises cost and risk while improving user experience - an approach that could add value in NHS services.